Experimental investigation of coating in a diesel engine for improved exhaust emissions and performance - Hazar, Hanbey; Öztürk, Ali Uğur (My University, 2016)
In this study, adiabatic property was brought to a 4-cylinder natural aspirated, direct injection diesel engine. For this purpose, cylinder liner, piston upper surface and valves were coated with powder with boron. Solid-boronizing method and plasma spray method were used as coating method. While cylinder liner and valves were coated with the layer of Fe2B in the thickness of 150 micron by using solid boronizing method, piston upper surface was coated with the layer of CoNiCrAlYttra +NiCrBSi in the thickness of 300 micron by using plasma spray method. After the coating process, the engine was subject to performance and emission tests. ASTM-D-2 fuel was used as test fuel. As a result of tests, while BSFC value of coated engine decreased at the rate of 7.5% and BSEC value decreased at the rate of 7% and at the rate of 15% in EGT value. While a decrease was observed at the rate of 10% in CO value, 47% in HC value, and 14% in Smoke value, an increase was observed at the rate of 35% in NOx value.
Keywords: Mühendislik; Makine; Malzeme Bilimleri; Kaplamalar ve Filmler